2008
DOI: 10.4049/jimmunol.180.9.6085
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen-Related Cell Adhesion Molecule 1 Inhibits Proximal TCR Signaling by Targeting ZAP-70

Abstract: The long cytoplasmic tail (CT) isoforms of carcinoembryonic Ag-related cell adhesion molecule 1 (CEACAM1) are expressed on activated human T cells and possess two ITIM motifs in the CT. These isoforms of CEACAM1 are inhibitory for T cell responses initiated by the TCR/CD3 complex with the inhibition dependent upon the ITIMs of CEACAM1 and Src homology 2 domain-containing phosphatase 1 (SHP-1). However, the mechanism by which this inhibition occurs in T cells is unknown. We demonstrate here that the Src family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
86
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(95 citation statements)
references
References 52 publications
8
86
0
1
Order By: Relevance
“…This is consistent with previous observations that the tyrosines within the CEACAM1-L ITIMs are phosphorylated by c-Src kinase in epithelial cells, Lck kinase in T cells, Btk kinase in B cells, Lyn in neutrophils, and insulin receptor as well as epidermal growth factor receptor tyrosine kinases in hepatocytes (Brummer et al, 1995;Skubitz et al, 1995;Abou-Rjaily et al, 2004;Pantelic et al, 2005;Dubois et al, 2006;Chen et al, 2008;Muller et al, 2009). We have previously shown in a mouse colon tumor model that CEACAM1-L acts as a tumor growth inhibitor.…”
Section: Journal Of Cell Science 123 (24)supporting
confidence: 81%
See 3 more Smart Citations
“…This is consistent with previous observations that the tyrosines within the CEACAM1-L ITIMs are phosphorylated by c-Src kinase in epithelial cells, Lck kinase in T cells, Btk kinase in B cells, Lyn in neutrophils, and insulin receptor as well as epidermal growth factor receptor tyrosine kinases in hepatocytes (Brummer et al, 1995;Skubitz et al, 1995;Abou-Rjaily et al, 2004;Pantelic et al, 2005;Dubois et al, 2006;Chen et al, 2008;Muller et al, 2009). We have previously shown in a mouse colon tumor model that CEACAM1-L acts as a tumor growth inhibitor.…”
Section: Journal Of Cell Science 123 (24)supporting
confidence: 81%
“…Previous studies have shown that tyrosine phosphorylation of CEACAM1-L within the ITIM motif is crucial for its function, including the regulation of signaling pathways in epithelial and immune cells (Huber et al, 1999;Izzi et al, 1999). Upon tyrosine phosphorylation, CEACAM1-L can bind SH2 domain-containing proteins, thereby activating Src-family tyrosine kinases and the protein tyrosine phosphatases SHP-1 and SHP-2 (Huber et al, 1999;Poy et al, 2002;Dubois et al, 2006;Chen et al, 2008;Klaile et al, 2009;Muller et al, 2009). We therefore evaluated whether CEACAM1-L was phosphorylated in response to VEGF treatment of endothelial cells and whether SHP-1 and the Src-like kinases played a role in CEACAM1-mediated endothelial phenotypes.…”
Section: Ceacam1 Is Tyrosine-phosphorylated Upon Vegf Treatment In a mentioning
confidence: 99%
See 2 more Smart Citations
“…Cette association faciliterait le recrutement de SHP-1 dans le complexe TCR/CD3, induisant la déphosphoryla-tion de la protéine Zap-70, kinase essentielle à l'activation du complexe. L'activation des voies de signalisation en aval de Zap-70 serait alors fortement inhibée [29]. S'ajoute à ce mécanisme l'intervention d'autres partenaires.…”
Section: Revuesunclassified